Inadequate description of placebo and sham controls in a systematic review of recent trials. (30th September 2019) - Webster, Rebecca K.; Howick, Jeremy; Hoffmann, Tammy; Macdonald, Helen; Collins, Gary S.; Rees, Jonathan L.; Napadow, Vitaly; Madigan, Claire; Price, Amy; Lamb, Sarah E.; Bishop, Felicity L.; Bokelmann, Klara; et al.
Abstract: Background: Poorly described placebo/sham controls make it difficult to appraise active intervention benefits and harms. The 12‐item Template for Intervention Description and Replication (TIDieR) checklist was developed to improve the reporting of active interventions. The extent to which TIDieR has been used to improve description of placebo or sham control is not known. Materials and methods: We systematically identified and examined all placebo/sham‐controlled randomised trials published in 2018 in the top six general medical journals. We reported how many of the TIDieR checklist items were used to describe the placebo/sham control(s). We supplemented this with a sample of 100 placebo/sham‐controlled trials from any journal and searched Google Scholar to identify placebo/sham‐controlled trials citing TIDieR. Results: We identified 94 placebo/sham‐controlled trials published in the top journals in 2018. None reported using TIDieR, and none reported placebo or sham components completely. On average eight TIDieR items were addressed, with placebo/sham control name (100%) and when and how much was administered (97.9%) most commonly reported. Some items (rationale, 8.5%, whether there were modifications, 25.5%) were less often reported. In our sample of less well‐cited journals, reporting was poorer (average of six items) and followed a similar pattern. Since TIDieR's first publication, six placebo‐controlled trials have cited it according to Google Scholar. Two of these used the checklist to describe placebo controls; neither one completely desribed the placebo intervention. Conclusions: Placebo and sham controls are poorly described within randomised trials, and TIDieR is rarely used to guide these descriptions. We recommend developing guidelines to promote better descriptions of placebo/sham control components within clinical trials.